Carbon nanotube–graphene-based nanofluids: a comprehensive review on the role of thermal conductivity and its solar energy applications - Bharadwaj, Gaurav; Sharma, Kamal; Pandey, Adarsh Kumar *; Gupta, Aayush (Springer, 2024)
Nowadays, nanofluids are considered as excellent working fluids with good thermophysical properties for augmenting the heat transfer in solar systems. Consisting of single-phase nanopowder, metal oxide-based nanofluids exhibit either a good thermal network or good physicochemical properties. Allotropes of carbon (e.g., carbon nanotubes; CNTs and graphene) have their own set of distinct structural and thermal properties to enhance the thermophysical properties of base fluids (e.g., water, ethylene glycol, etc.). For working fluids, researchers tried to optimize the preparation methodology in which a two-step method has been preferred due to the synergistic involvement of solid (i.e., particulate) and liquid (i.e., base fluid) phase. Also, several research groups have discussed the thermal behavior of different nanofluids with the help of correlations. A combination of MgO and CNTs has also been studied thoroughly to distinguish the effect of temperature and concentration of solid phase on the thermal conductivity of nanofluid. Further, CNT/graphene-based nanofluids serve a critical role in improving the thermal performance of solar collectors, solar stills, solar ponds, and solar cookers. It can also be utilized to reduce the surface temperature of solar cells in photo voltaic thermal (PV/T) systems which in turn increases the electrical efficiency of these systems. The present work illustrates a detailed review on the CNT/graphene-based nanofluids and their structural features for different solar energy applications.